2007
DOI: 10.1002/jez.416
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression profile of the ovarian cytochrome P‐450 aromatase (cyp19A1) gene during thermolabile sex determination in pejerrey, Odontesthes bonariensis

Abstract: Cytochrome P450 aromatase (cyp19) is an enzyme that catalyzes the conversion of androgens to estrogens and may play a role in temperature-dependent sex determination (TSD) of reptiles, amphibians, and fishes. In this study, the ovarian P450 aromatase form (cyp19A1) of pejerrey Odontesthes bonariensis, a teleost with marked TSD, was cloned and its expression profile evaluated during gonadal differentiation at feminizing (17 degrees C, 100% females), mixed-sex producing (24 and 25 degrees C, 73.3 and 26.7% femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 72 publications
2
57
0
2
Order By: Relevance
“…During the same period, cyp19a1 expression remained low at MPT. A previous study using semi-quantitative PCR noted a correlation between the proportions of larvae with increased cyp19a1 expression during the gonadal sex differentiation period and the percentages of females and suggested that cyp19a1 was related to ovarian differentiation in pejerrey (Karube et al, 2007). The results of this study provide confirmation to those findings and are in agreement with results obtained in other teleosts (Kitano et al, 1999;D'Cotta et al, 2001) and reptiles (Jeyasuria and Place, 1997;Gabriel et al, 2001;Murdock and Wibbels, 2003b;Ramsey and Crews, 2007;Rhen et al, 2007) with TSD.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…During the same period, cyp19a1 expression remained low at MPT. A previous study using semi-quantitative PCR noted a correlation between the proportions of larvae with increased cyp19a1 expression during the gonadal sex differentiation period and the percentages of females and suggested that cyp19a1 was related to ovarian differentiation in pejerrey (Karube et al, 2007). The results of this study provide confirmation to those findings and are in agreement with results obtained in other teleosts (Kitano et al, 1999;D'Cotta et al, 2001) and reptiles (Jeyasuria and Place, 1997;Gabriel et al, 2001;Murdock and Wibbels, 2003b;Ramsey and Crews, 2007;Rhen et al, 2007) with TSD.…”
Section: Discussionsupporting
confidence: 83%
“…In teleosts with TSD temperature also appears to regulate gonadal aromatase (cyp19a1) expression (Kitano et al, 1999;D'Cotta et al, 2001;Uchida et al, 2004). In the pejerrey, cyp19a1 showed a sexually dimorphic expression pattern during the first stages of ovarian differentiation and was proposed as a female molecular marker (Karube et al, 2007). However, to the best of our knowledge, the interplay and expression balance between dmrt1 and cyp19a1 at individual levels have not been analyzed so far in fish or any other species with TSD.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…2 ) [D'Cotta et al, 2001b;Baroiller et al, 2008]. Elevated cyp19a1 levels have also been found in the pejerrey O. bonariensis fry reared at female promoting temperatures (FPT) of 17 ° C after 6 wph, preceding histological differentiation [Karube et al, 2007;Fernandino et al, 2008b]. Similarly high expression levels of cyp19a1 were found in larvae of Japanese flounder reared at feminizing low temperatures of 18 ° C, but down-regulation occurred in offspring reared at the elevated male promoting temperatures of 27 ° C [Kitano et al, 1999].…”
Section: Environmental Effects On Sex At the Molecular Levelmentioning
confidence: 91%
“…In pejerrey, the critical or temperature-sensitive period occurs from the first to the fifth week after hatching, depending on temperature. Pejerrey larvae reared from hatching at 13-19ºC produced 100% females, at 29ºC 100% males, and mixed sex proportions at intermediate temperatures, 24-25ºC (Strüssmann et al, 1996b(Strüssmann et al, , 1997Karube et al, 2007;Fernandino et al, 2008a). Sex differentiation is also accelerated by rearing temperature; the ovarian differentiation occurs before at 24ºC than at 17ºC, whereas testis development takes place before at 29ºC than at 24ºC (Ito et al, 2005;Fernandino et al, 2008b).…”
Section: Introductionmentioning
confidence: 97%